Fuzzy Delphi Approach in The Development of a Human Model of Moral Education for Juvenile in Malaysian Prison Schools - Ashotha Krishnan; Vishalache Balakrishnan; Zaharah Hussin (Universitas Pendidikan Ganesha, 2022)
The development and revision of the new curriculum currently brings changes in rapidly growing trends. In fact, this discipline is also being innovated in the form of a new dimension known as the futuristic curriculum or the future curriculum. In this 21st era, the future curriculum is seen as one of the requirements for designing, planning, implementing and evaluating an educational policy or policy. This study examines the application of the Soft Model of Moral Education for adolescents in Malaysian prison schools using the Fuzzy Delphi approach. The purpose of this study was to obtain expert views on the development of this model in the Moral Education curriculum, specifically for students in prison schools. Fuzzy Delphi (FDM) technique was used to obtain expert consensus by distributing instruments to 23 selected experts from various fields and backgrounds to answer research questions. The findings of the study showed that the expert group consensus was over 75% by noting 88% - 92% for each component in this model. In addition, the threshold value for most of the sub-items is 0.2 and a fuzzy score must be equal to or greater than 0.5 has also been achieved for all elements which is between 0.87-0.92. Overall, the expert consensus is